2008
DOI: 10.1029/2008jd010137
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the dependence of clear‐sky top‐of‐atmosphere outgoing longwave radiation on atmospheric temperature and water vapor

Abstract: [1] We have analyzed observations of clear-sky top-of-atmosphere outgoing longwave radiation (OLR) measured by the Clouds and the Earth's Radiant Energy System (CERES). These measurements were obtained during March 2005 at night and over the ocean and cover latitudes from 70°N to 70°S. First, we compare the OLR measurements to OLR calculated from two radiative transfer models. The models use as input simultaneous and collocated measurements of atmospheric temperature and atmospheric water vapor made by the Atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…Clear-sky OLR from CERES-EBAF data is derived only from measurements over clear-sky atmospheric columns which are generally drier than the clear part of a cloudy atmospheric CERES column. Because a drier atmospheric column leads to a stronger OLR (e.g., Spencer and Braswell, 1997;Dessler et al, 2008;Roca et al, 2012), OLR clear from CERES-EBAF should overestimate OLR clear from C3M on average. The diurnal cycle, which is taken into account in OLR clear from CERES-EBAF but not in OLR clear from C3M (since we only used nighttime observations) could also play a role in the difference.…”
Section: Gridded Olrmentioning
confidence: 99%
“…Clear-sky OLR from CERES-EBAF data is derived only from measurements over clear-sky atmospheric columns which are generally drier than the clear part of a cloudy atmospheric CERES column. Because a drier atmospheric column leads to a stronger OLR (e.g., Spencer and Braswell, 1997;Dessler et al, 2008;Roca et al, 2012), OLR clear from CERES-EBAF should overestimate OLR clear from C3M on average. The diurnal cycle, which is taken into account in OLR clear from CERES-EBAF but not in OLR clear from C3M (since we only used nighttime observations) could also play a role in the difference.…”
Section: Gridded Olrmentioning
confidence: 99%
“…This effort aims to estimate longwave spectral flux and broadband OLR directly from AIRS Level 1 calibrated radiances over each individual single footprint. This approach is different from other studies such as Dessler et al (2008), Moy et al (2010) and Susskind et al (2012), which fed temperature and humidity fields from AIRS Level 2 retrievals (defined for threeby-three AIRS footprints) or even the Level 3 monthly gridded data set into a radiative transfer model to compute the clear-sky OLR. Huang et al (2008Huang et al ( , 2010Huang et al ( , 2014 and Chen et al (2013) have demonstrated that such direct estimate of spectral flux from AIRS radiances is feasible, and the estimated OLR highly agree with the collocated CERES OLR.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, polar-orbited hyperspectral infrared (IR) sensors, such as Atmospheric Infrared Sounder (AIRS) and Infrared Atmospheric Sounding Interferometer (IASI), have been popular in retrieving high-quality WV, especially UT WV, information on a global scale with high spatial resolution (Aires et al 2002, Divakarla et al 2006. Dessler et al (2008) illustrated that the calculated clear-sky top-of-atmosphere outgoing long-wave radiation from two radiative transfer models (RTMs) driven by moisture profiles retrieved from AIRS have excellent agreement with measurements from another satellite instruments, that is, the Clouds and the Earth's Radiant Energy System (CERES). However, the relatively short history of the hyperspectral data set limits its application in climate studies.…”
Section: Introductionmentioning
confidence: 99%